City, the place of society: a framework of architecture and community development - Schutte, Nathan Jeromie (Kansas State University, 2012)
Community development and architecture approach the study of the city in distinct ways while sharing the purpose of creating or modifying the places we inhabit. Community development utilizes a scientific approach through the study of place-making, developing it from a socially based tradition, in other words, communities of place. Architecture considers the city like a work of art approaching the study from a physical perspective and emphasizing form. Architecture in this context is both an element of construction in space and the totality of the construction, the whole of a community’s modification of site. Developed from the point of view of an architect, this investigation challenges the distinction between architecture and community development exploring each perspective’s study of the city. Through a linear progression of framework diagrams, modified as the result of connecting concepts between the two disciplines, this investigation demonstrates how architecture and community development can achieve a unified framework for the study of the city.
Keywords: City; Place; Society; Urban Artifact; Community Capital; Architecture (0729); Area Planning and Development (0341); Urban Planning (0999)